Comparison and Review Prosody of Seif - محمد امیر مشهدی; عبدالله واثق عباسی; محمدرضا مشهدی (مطالعات زبانی و بلاغی)
Imagery such as simile in traditional poem has two major tasks explaining and describing the thought, and decorating and arranging the speech. Simile as the most applicable imagery in poems of Naser Khosro is a tool for explaining and describing the poet's mind and less has been considered as an artistic and decorating element. The main purpose of this study is examining the vehicle in the complete works of Naser Khosro and of course vehicle was chosen because it draws the environment, ideology and the internal world of the poet. It's variation of vehicles is considerable in the complete works of Naser Khosro which we divided it's most important types into 3 groups in this article, including: nature and the elements related to it, like animals and mountains, group two includes cultural issues like religious and mythic concepts, features of aristocracy, behaviors in dressing and eating, and the third group includes daily observations of the poet.